Some Themes in Suárez’s Account of the Separated Soul - South, James B. (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
In this article, I focus on three issues in Francisco Suárez’s account of the separated soul: the status of the separated soul as a person, the separated soul’s knowledge of itself, and the question of the soul’s nature both as form of the body and as existing outside the body. I place his discussion in dialogue with St. Thomas Aquinas and Cajetan (Thomas de Vio) and show the ways he departs from those two thinkers. Finally, I show that his account of these problems makes for a philosophically probable account of the resurrection of the body.